Africa's changing farm size distribution patterns: the rise of medium‐scale farms. (November 2016) - Jayne, T.S.; Chamberlin, Jordan; Traub, Lulama; Sitko, Nicholas; Muyanga, Milu; Yeboah, Felix K.; Anseeuw, Ward; Chapoto, Antony; Wineman, Ayala; Nkonde, Chewe; Kachule, Richard
Abstract: This study assesses changes over the past decade in the farm size distributions of Ghana, Kenya, Tanzania, and Zambia, drawing on two or more waves of nationally representative population‐based and/or area‐based surveys. Analysis indicates that much of Sub‐Saharan Africa is experiencing major changes in farm land ownership patterns. Among all farms below 100 hectares in size, the share of land on small‐scale holdings under five hectares has declined except in Kenya. Medium‐scale farms (defined here as farm holdings between 5 and 100 hectares) account for a rising share of total farmland, especially in the 10–100 hectare range where the number of these farms is growing especially rapidly. Medium‐scale farms control roughly 20% of total farmland in Kenya, 32% in Ghana, 39% in Tanzania, and over 50% in Zambia. The numbers of such farms are also growing very rapidly, except in Kenya. We also conducted detailed life history surveys of medium‐scale farmers in each of these four countries and found that the rapid rise of medium‐scale holdings in most cases reflects increased interest in land by urban‐based professionals or influential rural people. About half of these farmers obtained their land later in life, financed by nonfarm income. The rise of medium‐scale farms is affecting the region in diverse ways that are difficult to generalize. Many such farms are a source of dynamism, technical change, and commercialization of African agriculture. However, medium‐scale land acquisitions may exacerbate land scarcity in rural areas and constrain the rate of growth in the number of small‐scale farm holdings. Medium‐scale farmers tend to dominate farm lobby groups and influence agricultural policies and public expenditures to agriculture in their favor. Nationally representative Demographic and Health Survey (DHS) data from six countries (Ghana, Kenya, Malawi, Rwanda, Tanzania, and Zambia) show that urban households own 5–35% of total agricultural land and that this share is rising in all countries where DHS surveys were repeated. This suggests a new and hitherto unrecognized channel by which medium‐scale farmers may be altering the strength and location of agricultural growth and employment multipliers between rural and urban areas. Given current trends, medium‐scale farms are likely to soon become the dominant scale of farming in many African countries.